Prevalence of Cutaneous Allergic Manifestations in patients with Allergic Asthma. A Cross-Sectional Study - Kashif Sardar, Nighat Fatima, Asma Bano, Imran Shehzad, Zahid Habib Qureshi, Bakhtawar Farooq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Asthma is a chronic inflammatory condition of the airways that is often related to atopic diseases, such as other allergic skin reactions. Allergic asthma is often associated with other allergic skin conditions like eczema, urticaria, and atopic dermatitis because of the common immunological and inflammatory mechanisms including eosinophilic inflammation and high levels of immunoglobulin E (IgE). The associated skin manifestations may help to elucidate and control systemic allergic disease. Objective: To assess the prevalence and the clinical spectrum of the cutaneous allergic manifestations in allergic asthma patients and their relationship to asthma severity and allergic biomarkers. Methods: The study was a cross-sectional observational study carried out from June 2022 to February 2023 in the Department of Pulmonology and Department of Dermatology of Multan Medical & Dental College, Multan, Pakistan. Consequently, non-probability of consecutive sampling was used to include a total of 120 patients who had clinically diagnosed allergic asthma. A detailed medical history, dermatological examination, spirometry, serum immunoglobulin E (IgE) level and peripheral eosinophil count were assessed. Data analysis was done by SPSS version 26.0. Results: Among 120 allergic asthma patients, 67 (55.8%) demonstrated one or more cutaneous allergic manifestations. Eczema was the most frequently seen dermatological disorder in 27 (22.5%) patients, urticaria was seen in 18 (15.0%) patients. Other causes of itching that were noted included allergic contact dermatitis, generalized pruritus, and atopic dermatitis. The prevalence of cutaneous manifestations was found to be significantly higher in moderate and severe asthma patients as compared to mild asthma patients (p=0.004). Higher serum IgE levels and peripheral eosinophilia were more likely to be observed in patients with associated dermatologic allergic diseases. Conclusion: Skin allergic reactions are very common in patients with allergic asthma and are well correlated with the severity of asthma and allergic inflammatory markers. Diagnosis of skin allergic diseases at early age may help to promote the overall management of allergic asthma and the long-term prognosis. Keywords: Allergic asthma, eczema, urticaria, atopic dermatitis, allergic skin disorders, eosinophilia, serum IgE, cutaneous manifestations.